Expanding the phenotypic spectrum of BCS1L‐related mitochondrial disease. Issue 11 (18th October 2021) - Hikmat, Omar; Isohanni, Pirjo; Keshavan, Nandaki; Ferla, Matteo P.; Fassone, Elisa; Abbott, Mary‐Alice; Bellusci, Marcello; Darin, Niklas; Dimmock, David; Ghezzi, Daniele; Houlden, Henry; Invernizzi, Federica; et al.
Abstract: Objective: To delineate the full phenotypic spectrum of BCS1L‐ related disease, provide better understanding of the genotype–phenotype correlations and identify reliable prognostic disease markers. Methods: We performed a retrospective multinational cohort study of previously unpublished patients followed in 15 centres from 10 countries. Patients with confirmed biallelic pathogenic BCS1L variants were considered eligible. Clinical, laboratory, neuroimaging and genetic data were analysed. Patients were stratified into different groups based on the age of disease onset, whether homozygous or compound heterozygous for the c.232A>G (p.Ser78Gly) variant, and those with other pathogenic BCS1L variants. Results: Thirty‐three patients were included. We found that growth failure, lactic acidosis, tubulopathy, hepatopathy and early death were more frequent in those with disease onset within the first month of life. In those with onset after 1 month, neurological features including movement disorders and seizures were more frequent. Novel phenotypes, particularly involving movement disorder, were identified in this group. The presence of the c.232A>G (p.Ser78Gly) variant was associated with significantly worse survival and exclusively found in those with disease onset within the first month of life, whilst other pathogenic BCS1L variants were more frequent in those with later symptom onset. Interpretation: The phenotypic spectrum of BCS1L‐ related disease comprises a continuum of clinical features rather than a set of separate syndromic clinical identities. Age of onset defines BCS1L‐ related disease clinically and early presentation is associated with poor prognosis. Genotype correlates with phenotype in the presence of the c.232A>G (p.Ser78Gly) variant.